Exercise Deactivates Leukocytes in Asthma - Vieira, R. P.; Silva, R. A.; Oliveira-Junior, M. C.; Greiffo, F. R.; Ligeiro-Oliveira, A. P.; Martins, M. A.; Carvalho, C. R. F. (International Journal of Sports Medicine, 2014)
Leukocytes play a central role in asthma physiopathology. Aerobic training (AT) reduces leukocytes recruitment to the airways, but the effects of AT on some aspects of leukocytes activation in asthma are unknown. Therefore, the effects of 4 weeks of AT on airway inflammation, pulmonary and systemic Th2 cytokines levels, leukocytes expression of pro and anti-inflammatory, pro-fibrotic, oxidants and anti-oxidants mediators in an experimental model of asthma was investigated. AT reduced the levels of IL-4, IL-5, IL-13 in bronchoalveolar lavage fluid (BALF) (p<0.001), serum levels of IL-5, while increased BALF and serum levels of IL-10 (p<0.001). In addition, AT reduced leukocytes activation, showed through decreased expression of Th2 cytokines (IL-4, IL-5, IL-13; p<0.001), chemokines (CCL5, CCL10; p<0.001), adhesion molecules (VCAM-1, ICAM-1; p<0.05), reactive oxygen and nitrogen species (GP91phox and 3-nitrotyrosine; p<0.001), inducible nitric oxide synthase (iNOS; p<0.001), nuclear factor kB (NF-kB; p<0.001) while increased the expression of anti-inflammatory cytokine (IL-10; p<0.001). AT also decreased the expression of growth factors (TGF-beta, IGF-1, VEGF and EGFr; p<0.001). We conclude that AT reduces the activation of peribronchial leukocytes in a mouse model of allergic asthma, resulting in decreased airway inflammation and Th2 response.
Keywords: asthma; exercise; immunology; allergy; cytokines